2014
DOI: 10.1371/journal.pone.0107004
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 Is Essential for Early Steps during Schwann Cell Differentiation of Amniotic Fluid Stem Cells and Regulates Lipogenic Gene Expression

Abstract: Schwann cell development is hallmarked by the induction of a lipogenic profile. Here we used amniotic fluid stem (AFS) cells and focused on the mechanisms occurring during early steps of differentiation along the Schwann cell lineage. Therefore, we initiated Schwann cell differentiation in AFS cells and monitored as well as modulated the activity of the mechanistic target of rapamycin (mTOR) pathway, the major regulator of anabolic processes. Our results show that mTOR complex 1 (mTORC1) activity is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Previous studies have shown that hAFS cells could either differentiate into neural cells in vitro or produce neurotrophic factors in vivo (Chen et al, 2015;Preitschopf et al, 2014). Research on neural differentiation capability of adult stem cells found that hAFS cells could respond to neural induction faster.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hAFS cells could either differentiate into neural cells in vitro or produce neurotrophic factors in vivo (Chen et al, 2015;Preitschopf et al, 2014). Research on neural differentiation capability of adult stem cells found that hAFS cells could respond to neural induction faster.…”
Section: Discussionmentioning
confidence: 99%
“…High Oct4‐expressing single‐cell clones, derived from the CD117/2 population, were used in this study [21]. Cells were maintained in Chang media, as previously described [21].…”
Section: Methodsmentioning
confidence: 99%
“…High Oct4‐expressing single‐cell clones, derived from the CD117/2 population, were used in this study [21]. Cells were maintained in Chang media, as previously described [21]. Chondrocytes were provided by Danube University Krems and were cultured in Dulbecco's modified Eagle's medium (DMEM; Thermo Fisher Scientific, Waltham, MA, https://www.thermofisher.com) supplemented with 10% fetal calf serum, 2.5 mM l ‐glutamine (GE Healthcare, Pasching, Austria, http://www3.gehealthcare.com), 50 mg/l streptomycin sulfate (GE Healthcare), 30 mg/l penicillin (GE Healthcare), and 50 µg/ml ascorbic acid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations